Salon nail care with superficial self-disclosure vitalizes psychological state - Kawakubo, Atsushi; Oguchi, Takashi (Frontiers in Psychology, 2023)
Physical attractiveness has long been established as a desirable trait in society. Physically attractive individuals are considered more competent, successful, and sociable. Numerous studies have examined the influence of makeup on physical attractiveness and its subjective psychological effects. However, the effect of nail care has not yet been examined. This study aimed to explore the psychological effects of nail care. Female Japanese participants (N = 334) completed an online questionnaire. The results showed that nail care positively elevated three aspects: positive emotions, relaxation, and vitalization. Moreover, they confirmed significant differences between receiving nail care from salon manicurists and self-performed nail care in terms of positive emotions and relaxation. The results indicated that nail care altered the appearance of the recipients' nails and their selfesteem, including their feelings, mood, and motivation. Furthermore, this study indicates that it may be preferable for both manicurists and clients not to self-disclose in-depth, as this would negate the positive effects of nail care. The study concludes with recommendations for future research.